Subclinical myopathy in patients with colorectal cancer: clinical-pathological characterization and search for tissue markers - Massimo Vecchiato; Sandra Zampieri; Stefano Merigliano (PAGEPress Publications, 2012)
Skeletal muscle in patients with cancer undergoes many morphological changes due to immuno-inflammatory factors of tumor origin or treatment.T he latest event of these changes is cancer cachexia. Aim of the study is to identify myopathic features in skeletal muscle biopsies from weight stable patients with colorectal cancer and without cachexia or asthenia / weakness, that could possibly provide new diagnostic and prognostic cancer biomarkers. Morphometric analyses and immunohistochemical studies were performed on intraoperative muscle biopsies from patients with colorectal cancer and from weight stable patients undergoing surgery for benign non-inflammatory conditions. A rectus abdominis biopsy was taken in all patients and controls.A correlation between histopathologic findings and clinical characteristics, circulating inflammatory biomarkers and markers of muscle necrosis,surgery data and cancer phenotype were investigated.. Forty four patients (21male/23 female) and 17 controls (6 male/11 female) (p=NS) were studied. In cancer patients’biopsies we observed asubclinical myopathy characterized by an abnormal distribution of myonuclei, which are localized inside the myofiber rather than at the periphery, and by the presence of regenerating muscle fibers. The percentage of myofibers with internalized nuclei is significantly higher in patients (median= 9%, IQR= 3.7-18.8) than in controls (median= 2.7%, IQR= 1.7-3.2) ( p=0.0002). In patients we observed an inverse correlation between the number of centronucleated fibers and the presence of node metastasis (N+)(ρ)=-0.64 (p=0.002). Patients affected with colorectal cancer display early sign of a myopathy, characterized by centronucleated and regenerating myofibers. This myopathy appears to be associated with an early stage of neoplasia and it could be an adaptive response of muscle to cancer. We hope a future application of these findings as a possible early diagnostic and prognostic biomarker of neoplasia.